Thermal conductivity evaluation of magnetized non-Newtonian nanofluid and dusty particles with thermal radiation - Hussain Syed Modassir; Khan Umair; Obalalu Adebowale Martins; Zaib Aurang (High Temperature Materials and Processes)
The thermal conductivity of nanofluids (NFs) has emerged as a critical area of research due to its potential to enhance heat transfer in various industrial applications. Non-Newtonian NFs, in particular, exhibit unique flow characteristics under the influence of magnetic fields, making them suitable for systems requiring precise control of fluid dynamics, such as cooling systems in electronics and energy sectors. Owing to its usage, this article presents the magneto-Marangoni convective flow for fluid (phase-I), particle (phase-II), and propagation in tangent hyperbolic NF (copper–ethanol) containing maximum cell swimming speed. This study aims to evaluate the thermal conductivity of magnetized non-Newtonian NFs mixed with dusty particles in the presence of thermal radiation, exploring how magnetic fields and particle interactions affect overall thermal performance. The Gegenbauer wavelet collocation-based scheme was utilized to solve the model and investigate physical attributes such as plate friction, Nusselt number, Sherwood number, and mass flux. The results indicate that the species reaction field is increased by activation energy, whereas it is reduced by chemical reaction. Also, increasing values of thermal radiation tend to improve the heat distribution.